1995
DOI: 10.4065/70.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Sarcoma: Diagnosis and Postoperative Follow-Up With Gadolinium-Diethylenetriamine Pentaacetic Acid-Enhanced Magnetic Resonance Imaging

Abstract: Pulmonary artery sarcomas are infrequently encountered and are often misdiagnosed before surgical exploration or autopsy. On clinical examination and conventional imaging studies, they are frequently mistaken for pulmonary emboli. To our knowledge, this case report is the first to describe the postoperative magnetic resonance imaging (MRI) appearance of residual disease of a pulmonary artery sarcoma and to assess the potential usefulness of MRI for monitoring such lesions postoperatively. Contrast-enhanced MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…An absence of deep vein thrombosis and the prolonged administration of anticoagulant or anti-thrombolytic agents may also suggest a diagnosis of pulmonary artery sarcoma. Some studies have found that gadolinium-enhanced magnetic resonance imaging is useful for distinguishing tumors from thrombi (11,12). Additionally, one study has shown that FDP-PET is useful for diagnosing intimal sarcoma (13).…”
Section: Discussionmentioning
confidence: 99%
“…An absence of deep vein thrombosis and the prolonged administration of anticoagulant or anti-thrombolytic agents may also suggest a diagnosis of pulmonary artery sarcoma. Some studies have found that gadolinium-enhanced magnetic resonance imaging is useful for distinguishing tumors from thrombi (11,12). Additionally, one study has shown that FDP-PET is useful for diagnosing intimal sarcoma (13).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, heterogenous enhancement on MRI after application of gadolinium-diethylene-triamine-pentaacetic acid is characteristic of a vascularized tumor. 7 The usefulness of biopsy via cardiac catheterization to make an accurate preoperative diagnosis has also been reported in the literature. 8 In the present case, a solid mass presented with low signal intensity on T1-weighted image and increased signal intensity on T2-weighted image by MRI and there was no evidence of distal thromboembolism in either of the pulmonary arteries on CT or MRI examination.…”
Section: Discussionmentioning
confidence: 99%
“…Extraluminal extension of the tumour can be a specific finding of PAS. Magnetic resonance imaging (MRI) aids the determination of the extent of masses and the relationship to adjacent structures, and during postoperative follow-up [4]. The degree of contrast enhancement in MRI was shown to correlate with the degree of tumour differentiation, and contrast enhancement might be used to differentiate neoplasm from central pulmonary embolism [5].…”
Section: Fdg-pet In Diagnostic Work-up Of Pulmonary Artery Sarcomasmentioning
confidence: 99%